High incidence of subclinical peripheral artery disease in people with HIV. (1st August 2022) - Suarez-Zdunek, Moises Alberto; Høgh, Julie; Kirkegaard-Klitbo, Ditte Marie; Jensen, Anne Marie R.; Rupert, Adam; Trøseid, Marius; Gerstoft, Jan; Nielsen, Susanne D.; Knudsen, Andreas D.
Abstract : Objective: Atherosclerosis is common in people with HIV (PWH). Peripheral artery disease (PAD) is the peripheral manifestation of atherosclerosis, but little is known about the incidence of PAD in PWH. Our objective was to determine the PAD incidence in PWH and to investigate potential risk factors. Design: Prospective longitudinal study on PWH from the Copenhagen Comorbidity in HIV Infection (COCOMO) study cohort. Methods: We performed ankle-brachial index (ABI) measurements at study entry and at 2-year follow-up and included participants with normal ABI at study entry. We defined de novo PAD as ABI ≤0.9 at follow-up. Using Poisson regression adjusted for age, sex, and smoking, we investigated the role of traditional and HIV-related risk factors, including inflammatory markers. Results: Of 844 PWH followed for a median duration of 2.3 years, 30 (3.6%) developed de novo PAD. All cases were subclinical. Diabetes (relative risk [RR] = 4.90 [95% confidence interval [CI]: 1.99–12.1]), current CD4 + cell count <350 cells/μl (2.66 [1.06–6.71]), longer duration of antiretroviral therapy (antiretroviral therapy [ART], 1.88 [1.06–3.33] per decade), and concentrations of high-sensitivity C-reactive protein (1.33 [1.08–1.63] per doubling) and interleukin-6 (1.38 [1.06–1.80] per doubling), were associated with de novo PAD. Conclusions: PWH had a high incidence of de novo subclinical PAD. Diabetes, low current CD4 + cell count, duration of ART, and inflammatory markers were associated with de novo PAD, indicating a possible role in PAD pathogenesis in PWH.